Analisis Faktor-Faktor yang Mempengaruhi Produktivitas Tenaga Kerja Pemanen Tandan Buah Segar di Perkebunan Sawit Rakyat Desa Hadundung Kecamatan Kota Pinang Provinsi Sumatera Utara - Putra Lukmana Yunus Hasibuan; Yusniar Lubis; Mitra Musika Lubis (Universitas Medan Area, 2021)
This research aims to determine the effect of wages, work experience, age and training on labor productivity in harvesters of fresh fruit bunches in smallholder oil palm plantations in Hadundung Village, Kota Pinang District, Labuhanbatu Selatan Regency. This research was conducted from March to April 2020. This study used the sampling method by means of the census method. The sample used is 42 respondents. The samples in this study were smallholder oil palm plantation harvesters. Based on the research results obtained from the results of the t test on the Wage Level variable has a significant effect on Labor Productivity with a significant value of 0.002, the age variable has a significant effect on Labor Productivity. This can be seen from the significant value of 0.000, it can be concluded that the Age variable has a significant effect on Labor Productivity and Training has a significant effect on Labor Productivity. With a significant value of 0.001. Whereas experience has no effect on labor productivity. This can be seen from the significant value 0.516 0.05. So it can be concluded that the experience variable has no effect on labor productivity.